2017
DOI: 10.3389/fmars.2017.00114
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Optical Properties of Two Neigboring Coastal Regions of Tropical Northern Australia: The Van Diemen Gulf and Darwin Harbour

Abstract: This study focuses on the seasonal and spatial characterization of inherent optical properties and biogeochemical concentrations in the Van Diemen Gulf and Darwin Harbour, two neighboring tropical coastal environments of Northern Australia that exhibit shallow depths (∼20 m), large (>3 m) semi-diurnal tides, and a monsoonal climate. To gain insight in the functioning of these optically complex coastal ecosystems, a total of 23 physical, biogeochemical, and optical parameters were sampled at 63 stations during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
(106 reference statements)
3
6
0
Order By: Relevance
“…9 showing the triangular classification of coastal waters based on the three optical components CDOM, phytoplankton and detritus at three different wavebands (443, 555, and 670 nm). During the study period, highest contribution to the absorption budget was from detritus at 555 nm; this has also reported by (Blondeau-patissier et al, 2017;Spyrakos et al, 2017). Similarly, detritus absorption showed a slightly decreasing trend at 670 nm while compared to 443 and 555 nm.…”
Section: Variability In Phytoplankton Absorption (A Ph (λ))supporting
confidence: 76%
See 1 more Smart Citation
“…9 showing the triangular classification of coastal waters based on the three optical components CDOM, phytoplankton and detritus at three different wavebands (443, 555, and 670 nm). During the study period, highest contribution to the absorption budget was from detritus at 555 nm; this has also reported by (Blondeau-patissier et al, 2017;Spyrakos et al, 2017). Similarly, detritus absorption showed a slightly decreasing trend at 670 nm while compared to 443 and 555 nm.…”
Section: Variability In Phytoplankton Absorption (A Ph (λ))supporting
confidence: 76%
“…However, it required more efforts to characterize the bio-optical properties of coastal waters (Devred et al, 2013;Garaba et al, 2014;Mouw et al, 2015;Han et al, 2016). The coastal waters are influenced not only by phytoplankton and its byproducts, but also by other optically active substances (Moore et al, 2014;Barnes et al, 2014;Zhang et al, 2014aZhang et al, , 2014bSun et al, 2014) that vary independently of phytoplankton, like particles in suspension and CDOM (Blondeau-patissier et al, 2017;Menon et al, 2011;Tilstone et al, 2012;Brezonik et al, 2015;Pérez et al, 2016). CDOM is a part of the dissolved organic carbon (DOC) pool composed essentially fulvic and humic acid (Tiwari and Shanmugam, 2011;Organelli et al, 2014;Xing et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Chl-a and a phy values observed in this study were lower than expected for coastal waters (Costa et al, 2006;Blondeau-Patissier et al, 2017;Russell et al, 2019), although comparable with average values reported for Case-1 waters (Bricaud et al, 2004(Bricaud et al, , 2010. The distinctive oceanographic conditions in the study region might be responsible for such low phytoplankton biomass as the influence of the nutrient-poor Brazil Current, which also promotes a nutrient wash with its flow, and the water column stratification in summer.…”
Section: Phytoplanktonsupporting
confidence: 76%
“…Since all the stations presented Sr values higher than 1 (i.e., S 275-295 ≥ S 350-400 ), there is probably a dominance of low molecular weight CDOM. Additionally, the exponential decrease found between S 275-295 and a CDOM (350) indicates possible effects of photobleaching for ABR samples (Fichot and Benner, 2012;Blondeau-Patissier et al, 2017). This study documented a spatial variability of the bio-optical properties in the Abrolhos Bank region but was limited by the relatively small number of in situ stations.…”
Section: Slopes Of Non-algal Particles and Dissolved Organic Mattermentioning
confidence: 65%
See 1 more Smart Citation